Empowering the Community Through Mental Health Cadre - Ulfa Husnul Fata; RR Dewi Rahmawaty; Erni Setiyorini; Wahyu Wibisono (Journal of Community Service for Health, 2023)
Mental health is important in individual life. Individuals should not only physically healthy, but also psychologically. Early detection of family mental health is one of the main pillars in promotive and preventive efforts that can be carried out by mental health cadre. Through mental health cadre training activities regarding the early detection of family psychological, mental health cadres have the knowledge and skills to understand the mental health conditions of a family. This community service activity regarding early detection of family mental health were carried out by lecturers of the Nursing Education Study Program and Students of Professional Practice of Nurses Transfer Levels during the academic year of 2022/2023. The method used in this activity was the delivery of materials, question and answer session, and continued by practice on how to detect early mental health in the families. These activities were conducted on Bacem Village, Ponggok District, Blitar Regency. The number of mental health cadre involved in this activity was 15 people. A healthy mental environment can be started by empowering families through early detection of cases of mental disorders by mental health cadre. The result revealed that through training activities on family mental health detection, mental health cadre have the knowledge and skills to carry out mental health detection in families.